In vitro determination of the efficacy of illicit synthetic cannabinoids at CB1 receptors. (10th December 2019) - Sachdev, Shivani; Vemuri, Kiran; Banister, Samuel D.; Longworth, Mitchell; Kassiou, Michael; Santiago, Marina; Makriyannis, Alexandros; Connor, Mark
Abstract : Background and Purpose: The morbidity and mortality associated with recreational use of synthetic cannabinoid receptor agonists (SCRAs) may reflect strong activation of CB1 receptors and is a major health concern. The properties of SCRA at CB1 receptors are not well defined. Here we have developed an assay to determine acute CB1 receptor efficacy using receptor depletion with the irreversible CB1 receptor antagonist AM6544, with application of the Black and Leff operational model to calculate efficacy. Experimental Approach: Receptor depletion in mouse AtT‐20 pituitary adenoma cells stably expressing human CB1 receptors was achieved by pretreatment of cells with AM6544 (10 μM, 60 min). The CB1 receptor‐mediated hyperpolarisation of AtT‐20 cells was measured using fluorescence‐based membrane potential dye. From data fit to the operational model, the efficacy ( τ ) and affinity ( K A ) parameters were obtained for each drug. Key Results: AM6544 did not affect the potency or maximal effect of native somatostatin receptor‐induced hyperpolarization. The τ value of ∆ 9 ‐THC was 80‐fold less than the reference CB receptor agonist CP55940 and 260‐fold less than the highest efficacy SCRA, 5F‐MDMB‐PICA. The operational efficacy of SCRAs ranged from 233 (5F‐MDMB‐PICA) to 28 (AB‐PINACA), with CP55940 in the middle of the efficacy rank order. There was no correlation between the τ and K A values. Conclusions and Implications: All SCRAs tested showed substantially higher efficacy at CB1 receptors than ∆ 9 ‐THC, which may contribute to the adverse effects seen with these drugs but not ∆ 9 ‐THC.